2022
DOI: 10.5055/jem.0606
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression among public health workers during the COVID-19 pandemic

Abstract: Introduction: The public health workforce plays an essential role in the response to disasters and emergencies. Little is known about the prevalence of anxiety and depression among the public health emergency preparedness workforce responding to COVID-19 or the potential for social support to protect public health workers from adverse outcomes.Methods: A cross-sectional online survey was conducted among a sample of the public health workforce participating in the response to COVID-19. Prevalence ratios (PRs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
(34 reference statements)
2
4
0
Order By: Relevance
“…Household size and children being present in the home were not found to be associated with either GAD or depression. These findings were consistent with prior risk factors reported by the authors in the original survey populations and elsewhere in the literature (Pfender et al 2022 ; Guilaran et al 2018 ; Prati and Pietrantoni 2010 ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Household size and children being present in the home were not found to be associated with either GAD or depression. These findings were consistent with prior risk factors reported by the authors in the original survey populations and elsewhere in the literature (Pfender et al 2022 ; Guilaran et al 2018 ; Prati and Pietrantoni 2010 ).…”
Section: Resultssupporting
confidence: 92%
“…We assessed social support with two questions from the Social Support Rating Scale (SSRC) that asked about available sources for support for comfort and caring and for economic support and practical problem solving. Sources of support included none, spouse/partner, other family members, friends, relatives, colleagues, companies, official or semi-official organizations such as parties, leagues, and unions, unofficial organizations such as religious organizations or social groups, and other (Xiao 1994 ; Pfender et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continued role-related challenges produced feelings of being overwhelmed and extremely tired, and feeling underappreciated, contributing to participants' emotional exhaustion, a tenet of burnout. This also aligns with a recent study that reported an association between higher emotional labor intensity and burnout among PHNs in South Korea on the frontlines of the COVID-19 pandemic (Kim et al, 2022) as well as other research examining effects of COVID-19 on clinical nurses in hospital settings (Arnetz et al, 2020;Guttormson et al, 2022;Kelley et al, 2021) and public health workers (Pfender et al, 2022;Stone et al, 2021). Burnout, like role strain, is associated with greater intention to leave the profession and turnover (Leiter & Maslach, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…Otherwise, an individual who is infected can easily create a breach in a community's pandemic prevention efforts, thereby endangering their family, their own safety and that of their colleagues and the public. Studies have indicated that nursing staff experienced considerable physical, mental and social stress during the COVID‐19 pandemic (Arnetz et al., 2020; Kelley et al., 2021; Motahedi et al., 2021; Pfender et al., 2022; Stone et al., 2021). Thus, an understanding of the complex and interrelated needs of frontline nurses can help health care organisations develop effective solutions for reducing stress in PHNs.…”
Section: Discussionmentioning
confidence: 99%